Role of Exercise in Preventing Diastasis Recti in Pregnant Women - Mumtaz, Syed Naveed; Kayani, Bushra Afzal; Shah, Syed Fahd (Pakistan Armed Forces Medical Journal, 2022)
Objective: To see the effect of exercise in preventing diastasis recti in pregnant women.Study Design: Prospective comparative study.Place and Duration of Study: Gynecology & Obstetrics, Avicenna Medical College, Lahore Pakistan, from Jan to Dec 2019.Methodology: This study included 93 pregnant women who were randomized in two groups, exercise group and non-exercise group. The measurement for diastasis recti abdomen was taken at 3 locations: at the umbilicus, 5 cm above the umbilicus, and 5 cm below the umbilicus. Measurement for diastasis recti were done at the time of inclusion in study and 6 weeks after the termination of pregnancy.Results: The mean age of the women in our study was 26.5 ± 0.62 years. The frequency of diastasis recti was far less in exercising pregnant women as compared to non-exercising pregnant ladies after 6-weeks postpartum period. No diastasis recti was present at the supra-umbilical level in 34 (36.55%) women of exercise-group as compared to 9 (9.67%) in non-exercise group. At supra umbilical level, there was no diastasis recti present in 43 (46.2%) women of exercise-group as compared to 7 (7.52%) women in non-exercising groups at 6-weeks postpartum period. Similarly, no diastasis recti were present in 43 (46.2%) women of exercise-group as compared to 8 (8.60%) women in non-exercising group at infra umbilical level at 6 weeks postpartum period. Result showed that there was statistically significant improvement in the diastasis recti abdominis in exercise-group (p=0.002).Conclusion: Abdominal exercises help in reducing diastasis recti in pregnant women significantly as compared..............................